Strategi Hamba Tuhan Dalam Membudayakan Literasi Membaca Alkitab Bagi Pertumbuhan Rohani Jemaat - Nirwan Lawolo; Dyulius Thomas Bilo (Sepakat : Jurnal Pastoral Kateketik, 2023)
The Bible is God's Word written by the prophets through His guidance and also through God's breath itself in ancient times. As God's creation, church people need to build relationships through the intimacy of reading, contemplating and carrying out God's heart through God's Word contained in the Bible. In fact, most Christians and even young people think that this is not important so that there is a tendency for church members to rarely read the Bible. Therefore, the strategy of God's servant is really needed in motivating church members so that the love of reading the Bible increases and continues to be maintained for the continuity of church discipleship and the spiritual growth of mature congregations. This study aims to describe the duties of a servant of God in carrying out his duties as a pastor of the congregation and how the church creates devices, facilities, programs, methods or technology in order to motivate the congregation to cultivate reading the Bible in creative ways, as well as to guide and direct the congregation to grow in the knowledge of God and to accompany each member of the congregation to grow spiritually to mature one's faith in Jesus Christ.